KOMPARASI PELAKSANAAN TAKE OVER PADA BANK NEGARA INDONESIA SYARIAH DAN BANK RAKYAT INDONESIA DI PAREPARE - Zulfhaidz Husain; Muhammad Kamal Zubair; Damirah Damirah (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2019)
Take Over is an action carried out by users of banking services to move payments or installments that are considered more profitable by users of banking services, where in this case the Customer, the transfer made in the form of transfer of services, payments and installments that customers consider more profitable for them Use. The transfer of payment itself involves two different banking institutions where installments or financing that run from one bank to another are transferred according to the provisions of each banking institution involved in it. The results of this study indicate that there are several differences in take-over systems implemented by Bank Negara Indonesia Syariah and Bank Rakyat Indonesia, including the contract agreement system that exists in these two banking institutions, where Bank Negara Indonesia Syariah uses a system with a sharia contract, namely the contract is a profit sharing contract, which they apply is a Murabahah contract and guidelines for the rules and procedures carried out at Take Over are the foundation of the DSN-MUI Fatwa and all provisions contained in the land, then at the Bank Rakyat Indonesia the contract used is in accordance with the provisions of the party banking itself the interest rate applied to the Contract is a Flat (fixed and Floating) interest rate or a fixed interest rate with the provisions of the installment table in accordance with the provisions of the Bank Rakyat Indonesia.